Concordance of Child Self-Reported and Parent Proxy-Reported Posttraumatic Growth in Childhood Cancer Survivors - Koutná, Veronika; Blatný, Marek; Jelínek, Martin (Cancers, 2021)
This article aimed to analyze concordance of parent- and child-reported child posttraumatic growth (PTG) following pediatric cancer, the influence of the parents' own level of PTG on the level of concordance and the influence of the parents' and the child's own level of PTG on the parents' proxy reports of PTG in the child. The sample included 127 parent-child dyads. The children provided self-reports of PTG and the parents provided reports of their own as well as the child's PTG. Overall, the results showed poor parent-child agreement on the child PTG, with the parents proxy-reporting higher levels of PTG than the children. The parents' proxy reports of the child PTG were the most accurate at the lowest levels of the parents' own level of PTG. The parents' own level of PTG was a stronger predictor of the parents' proxy reports than the child self-reported PTG. The results suggest that parents are not very accurate reporters of PTG in the child; therefore, their reports should be completed with child self-reports whenever possible.